Strategic management and governance : strategy execution around the world - Joyce, Paul, 1952- (Abingdon ; New York, NY : Routledge, 2022)
"This book is an investigation into the evolving nature and consequences of strategic management in public governance. It is prompted by the practical as well as the academic interest in the application of strategic management to public governance and to the public sector. The main features of this book are its management focus, its use of published statistics and expert ratings to develop empirical insights into the capabilities and processes of strategic management in government, and its concern for practical relevance. Although this book deals with governments, it is a management book and not a political book. It is, in fact, a management book that "frames" strategic management in government as a tool of (or enabler of) the public governance process. This is relatively novel. The book's management focus has several themes, which can be summed up as comprising: the use by government of long-term strategic visions and strategies, effective management of the delivery of strategic visions and strategies, the performance of national governments, and the implications of strategic state capabilities for the quality of public services, for sustainability, and for managing strategic crises. This book will be relevant reading to researchers, scholars, advanced students, policy makers and public administrators in the fields of strategy, strategic management, and public governance"--
Strategic management and governance -- It's not easy -- Strategic visions and priorities -- Taking strategy seriously -- The whole-of-society approach -- Intelligent government acting in and for society -- Quality public services -- Sustainability and the 2030 agenda -- Strategic crisis management -- Strategic leaders -- A moment of renewal.
OCLC-licensed vendor bibliographic record.
Keywords: Strategic planning; Public administration; Organizational change; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Government & Business; BUSINESS & ECONOMICS / Development / Economic Development